PROGRAMMING WITH VISUAL BASIC BEGINNER - Khalid Isa; Zarina Tukiran (2006)
In the recent years Visual Programming especially Visual Basic are being used extensively in engineering and science systems development. This rapid progress in engineering and science fields has created an increasing demand for trained engineering and science personnel with programming skills. This book is intended for anyone with little or no programming experience to develop their skills in Visual Basic programming. It will also serve as reference material for students to learn about basic programming using Microsoft Visual Basic version 6.0. The fundamental concepts and principles behind Visual basic are explained in a simple, easy-to-understand manner. Each chapter contains a large number of solved problems which will help the students in problem solving and design software or application.